Assessing children's writing products: the role of curriculum based measures. (3rd December 2014) - Dockrell, Julie E.; Connelly, Vincent; Walter, Kirsty; Critten, Sarah
<x xml:space="preserve">Abstract</x> The assessment of children's writing raises technical and practical challenges. In this paper we examine the potential use of a curriculum based measure for writing (CBM‐W) to assess the written texts of pupils in Key Stage 2 (M age 107 months, range 88 to 125). Two hundred and thirty six Year three, five and six pupils completed a standardized assessment of writing quality. Pupils also responded to two writing probes, one expository and one narrative, at baseline and five months later. In response to the probe pupils wrote for five minutes. Transcribed texts were scored for productivity (total words produced, correct word sequences, number of punctuation marks and sentences produced) and accuracy (proportion of words spelled correctly, correct word sequences and punctuation marks). The CBM –W measures were differentially sensitive to development and showed construct validity as evidenced by their association with the norm‐ referenced test measuring writing quality. Change over time was also evident and significant differences between narrative and expository texts were found. Pupils with special educational needs scored significantly more poorly on the CBM‐W. Potential implications for research and practice are considered.